Fostering innovation through green HRM: The mediating role of organizational support and green commitment - Yunaningsih, Ani; Johan, Ahmad; Rahmayanti, Rima (Asian Management and Business Review, 2024)
This study aims to investigate the role of green human resource management (GHRM) on innovative work behavior in helping organizations to implement environmentally friendly business practices. By using natural resource-based view and social exchange theory as theoretical lens, we consider the role of green HRM, perceived organizational support for the environment, green knowledge sharing, and green commitment as antecedents of innovative work behavior. The sample is 215 employees from the MSME’s manufacturing industrial sector in West Java province selected using purposive sampling, then the data was analyzed using structural equation models (SEM-PLS). The research results show that GHRM practices have a positive and significant influence on green commitment, green knowledge sharing, and innovative work behavior. Apart from that, the moderating role of green knowledge sharing is found to strengthen the relationship between green human resource management and green commitment. The mediating role of green commitment in the relationship between GHRM and employee innovative work behavior is also confirmed. This study also found that organizational support indirectly influences green commitment. The findings of this study provide contribution to the literature, especially in the field of organizational behavior by emphasizing the role of GHRM practice to stimulate innovative work behavior of employees. It also provides practical implications for organizations to adopt environmentally friendly business practices as an effort to improve their positive outcomes of the employees.